Rancang Bangun Alat Pendeteksi Level Paparan Gas Formalin Pada Ruang Penyimpanan Laboratorium - Fadillah, Yudar; Budisusila, Eka Nuryanto; Suprajitno, Agus (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
Formalin is a hazardous chemical commonly used in laboratories, especially for specimen preservation. Ensuring safe handling and storage is crucial to minimize risks. This research aims to design and build a device to detect formaldehyde gas in laboratory storage rooms. The device uses a DFRobot formaldehyde gas sensor to detect formalin concentration, processed by Arduino and displayed on an LCD. It features a buzzer for alerts, a servo motor for exhaust control, and a DC fan for air circulation. The system is supported by an LM2596 step-down module and a 12V power supply. Results show the device effectively detects formaldehyde gas and provides warnings when concentrations exceed safe thresholds, while also reducing formalin levels through improved air circulation.